The Effect of Fixed Target and Moving Target Training Methods on Badminton Smash Performance at PB Muda Mandiri - M. Risky Novji Tiara; Tjung Hauw Sin (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Badminton smash accuracy is an important concern in athlete training because the smash is one of the most decisive attacking techniques for gaining points during a match. However, limited research has examined the use of fixed target and moving target training methods to improve smash performance among young athletes at PB Muda Mandiri. This study aims to analyze the effect of fixed target and moving target training methods on badminton smash performance. A quantitative approach was employed using a quasi-experimental design, involving 10 male badminton athletes selected through purposive sampling from a total population of 25 athletes at PB Muda Mandiri. Data were collected using a badminton smash performance test and analyzed through the Lilliefors normality test and t-test at a significance level of α = 0.05. The findings indicate that fixed target and moving target training methods significantly improved badminton smash performance. The average pre-test score was 12, while the average post-test score increased to 20 after the treatment. Hypothesis testing showed that t-count = 4.57 was higher than t-table = 1.833, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. The study concludes that fixed target and moving target training methods play an important role in enhancing badminton smash performance. These findings contribute to the development of badminton training methods by demonstrating the effectiveness of structured target-based exercises in improving smash accuracy. Practically, the study recommends that coaches integrate fixed target and moving target exercises into technical training programs, while future research should involve larger samples, control groups, and additional performance indicators such as smash speed, power, and match effectiveness.